2020
DOI: 10.1038/s41598-020-63384-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between vitiligo and smoking: A nationwide population-based study in Korea

Abstract: no study has examined the associations between vitiligo and smoking. the purpose of this study was to investigate the incidence of vitiligo according to smoking status. We used clinical data from individuals aged over 20 years who received a health examination in the National Insurance Program between 2009 and 2012 (n = 23,503,807). We excluded individuals with pre-existing vitiligo who had ever been diagnosed with vitiligo before the index year (n = 35,710) or who were diagnosed with vitiligo within a year of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…33 However, when it refers to the association between smoking and vitiligo, a retrospective study showed that smoking could decrease the risk of vitiligo concerning smoking dose. 34 Nevertheless, the authors of this study emphasised that smoking does not have a distinct benefit for vitiligo development. 34 It is worth mentioning that extensive clinical studies have established a strong association between smoking and the incidence and severity of vitiligo.…”
Section: Methodsmentioning
confidence: 81%
See 2 more Smart Citations
“…33 However, when it refers to the association between smoking and vitiligo, a retrospective study showed that smoking could decrease the risk of vitiligo concerning smoking dose. 34 Nevertheless, the authors of this study emphasised that smoking does not have a distinct benefit for vitiligo development. 34 It is worth mentioning that extensive clinical studies have established a strong association between smoking and the incidence and severity of vitiligo.…”
Section: Methodsmentioning
confidence: 81%
“…34 Nevertheless, the authors of this study emphasised that smoking does not have a distinct benefit for vitiligo development. 34 It is worth mentioning that extensive clinical studies have established a strong association between smoking and the incidence and severity of vitiligo. [35][36][37] The exposure to smoke has been discovered…”
Section: Methodsmentioning
confidence: 81%
See 1 more Smart Citation
“…18 A Korean study on systemic vitiligo found that smoking can decrease the risk of the condition. 19 The study analyzed a national cohort database and compared the incidence of vitiligo in nonsmokers and smokers. The results revealed that current smokers had a significantly lower risk of vitiligo than nonsmokers, with a hazard ratio of 0.51 and a 95% CI of 0.50, 0.53.…”
Section: Discussionmentioning
confidence: 99%
“…7 Interestingly, smokers were proven to have a higher ability to resist vitiligo development than their non-smoking counterparts according to a nationwide population-based study performed by Lee et al on Korean people. 8…”
Section: Introductionmentioning
confidence: 99%